2018
DOI: 10.1089/pho.2018.4438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Photobiomodulation on Partial Osteotomy in Streptozotocin-Induced Diabetes in Rats

Abstract: PBM significantly increased many stereological parameters of bone repair in an STZ-induced TIDM during catabolic response of fracture healing. Further RT-PCR test demonstrated that bone repair was modulated in diabetic rats during catabolic response of fracture healing by significant increase in mRNA expression of RUNX2, and osteocalcin compared to healthy control rats. PBM also decreased osteocalcin mRNA expression in TIDM rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous experiments have shown that PBM can promote bone healing in diabetic rat models by improving the viability of osteoblasts and mesenchymal cells ( 129 , 130 ). Experiments on diabetic rats proved that PBM treatment can improve the viability of osteoblasts, significantly increase the mRNA expression of RUNX2 and osteocalcin, and increase the activity of alkaline phosphatase and the production of the mineralized matrix, thereby regulating the bone healing process ( 131 , 132 ). In addition, PBM has also been shown to improve the survival, proliferation and apoptosis of BMSCs in diabetic rats ( 133 ).…”
Section: Physical Therapiesmentioning
confidence: 99%
“…Previous experiments have shown that PBM can promote bone healing in diabetic rat models by improving the viability of osteoblasts and mesenchymal cells ( 129 , 130 ). Experiments on diabetic rats proved that PBM treatment can improve the viability of osteoblasts, significantly increase the mRNA expression of RUNX2 and osteocalcin, and increase the activity of alkaline phosphatase and the production of the mineralized matrix, thereby regulating the bone healing process ( 131 , 132 ). In addition, PBM has also been shown to improve the survival, proliferation and apoptosis of BMSCs in diabetic rats ( 133 ).…”
Section: Physical Therapiesmentioning
confidence: 99%
“…Fact number four: Many studies have shown that PBM with 890 nm wavelength has positive photobiostimulatory effects on bone regeneration in partial osteotomy, and critical size femoral defects, of healthy, diabetic, and osteoporotic animals [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%